2012
DOI: 10.1063/1.3682768
|View full text |Cite
|
Sign up to set email alerts
|

Local structural models of complex oxygen- and hydroxyl-rich GaP/InP(001) surfaces

Abstract: We perform density-functional theory calculations on model surfaces to investigate the interplay between the morphology, electronic structure, and chemistry of oxygen-and hydroxyl-rich surfaces of InP(001) and GaP(001). Four dominant local oxygen topologies are identified based on the coordination environment: M -O-M and M -O-P bridges for the oxygen-decorated surface; and M -[OH]-M bridges and atop M -OH structures for the hydroxyl-decorated surface (M =In,Ga). Unique signatures in the electronic structure ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(92 citation statements)
references
References 76 publications
5
86
1
Order By: Relevance
“…Regarding solar-hydrogen genera tion for energy storage and renewable-fuel production, tandem structures reach optimum theoretical solar-to-hydrogen effi ciencies applying Si as substrate and 1.6 to 1.8 eV band-gap absorbers [3], The latter could be lattice-matched grown by dilute nitride Ga(N,As)P with theoretical photovoltaic tandem efficiencies close to optimum [4], GaP-related surfaces and their interfaces to water are the subject o f current theoretical [5][6][7] as w ell as experimental [8] studies, and the combination with Si(100) for photoelectrochemical (PEC) diodes is highly desired for water splitting [9], Pseudomorphic GaP/Si(100) serves as a quasisubstrate for the subsequent industrially scal able growth o f high-performance electronic and optoelectronic devices, such as multijunction solar cells [4,10] …”
Section: Introductionmentioning
confidence: 99%
“…Regarding solar-hydrogen genera tion for energy storage and renewable-fuel production, tandem structures reach optimum theoretical solar-to-hydrogen effi ciencies applying Si as substrate and 1.6 to 1.8 eV band-gap absorbers [3], The latter could be lattice-matched grown by dilute nitride Ga(N,As)P with theoretical photovoltaic tandem efficiencies close to optimum [4], GaP-related surfaces and their interfaces to water are the subject o f current theoretical [5][6][7] as w ell as experimental [8] studies, and the combination with Si(100) for photoelectrochemical (PEC) diodes is highly desired for water splitting [9], Pseudomorphic GaP/Si(100) serves as a quasisubstrate for the subsequent industrially scal able growth o f high-performance electronic and optoelectronic devices, such as multijunction solar cells [4,10] …”
Section: Introductionmentioning
confidence: 99%
“…semiconductors InP and GaP has been subject of several theoretical investigations [11][12][13], but experimental data only exists for InP(110) [14,15] and not for GaP to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…13,25 Oxygen exposure leads to a strong feature between 6 and 8 eV below E F . Compared to calculations of Wood et al, 10 this would point towards Ga-O-P as a structural motif, which is expected to exhibit the highest density of states in the energy range of the considered structures. The peak around 2.5 eV in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Several theoretical studies investigated this question for GaP(100) and InP(100) identifying surface motifs which can act as charge carrier traps. [9][10][11] Water adsorption studies in ultra-high vacuum (UHV) on cleaved InP(110) samples revealed the Figure 1. Ball-and-stick model of the III-rich, mixed dimer and the P-rich, hydrogen stabilized surface reconstructions, which are typical for MOVPE-prepared InP(100) and GaP(100).…”
Section: Introductionmentioning
confidence: 98%